Role of misfolded prion protein in neurodegeneration - Alibhai, James David (The University of Edinburgh, 2015)
Chronic neurodegenerative diseases, such as Alzheimer’s disease, prion diseases and many others are unified by the aberrant folding of a host encoded protein to a disease-associated isoform and the predictable cell-to-cell spread of disease-associated misfolded proteins via a putative prion-like mechanism. Prion diseases, for example, are associated with the aberrant folding of host encoded prion protein (PrPC) to a disease-associated isoform, which acts as a seed for the further conversion of PrPC to misfolded protein species. The role of misfolded prion protein in neurodegeneration remains unclear. Accumulation and spread of misfolded prion protein is typically slow and progressive, correlating with neurodegeneration. A number of studies show that mice are susceptible to prion disease with characteristic hallmarks of prion pathology but in the presence of little detectable misfolded prion protein (e.g. the GSS/101LL model). In this thesis I test the hypothesis that detectable species of misfolded prion protein correlate with neurodegeneration and spreads in a predictable, progressive fashion from one anatomically distinct brain region to the next. Using the GSS/101LL model, misfolded prion protein was detected as mostly PK-sensitive isoforms (PrPsen). The progression and pathological presentation is comparable to other prion diseases with larger quantities of PK resistant prion isoforms. A highly sensitive in vitro assay system (the QuIC assay) was subsequently used to establish the extent that misfolded protein was present within the brain. Amyloidogenic prion seeds were found to be widespread throughout the brain from an early stage and spread rapidly throughout the brain. Absence of neurodegeneration in certain brain regions is not due to differing quantities of prion seeds between regions or time exposed to prion seeds, as unaffected regions are exposed to comparative quantities of prion seeds for the same time-period as regions of the brain which eventually succumb to neurodegeneration. These results indicate a clear dissociation between prion seeds and neurotoxicity. They highlight the need to understand regional host responses to prion seeds that may evoke neurodegeneration in some but resilience in others. To test this, transcriptomic analysis was carried out on brain samples from regions undergoing neurodegeneration and unaffected regions. A gene profile signature of hybrid pro-and anti-inflammatory response was observed in regions undergoing neurodegeneration. However, large cohorts of genes were down-regulated across all regions tested, including pro-inflammatory genes and a large proportion of genes involved within transcriptional and translational regulation and function. These results highlight the possible molecular pathways in response to the presence of misfolded protein. In summary, misfolded prion protein accumulates rapidly across the CNS but only specific brain regions undergo neurodegeneration. In the presence of the misfolded protein, the host elicits a robust molecular response. The additional activation of glial cells within regions undergoing neurodegeneration highlights their importance in disease. It is therefore proposed that misfolded prion protein, alone, is not sufficient to trigger neurodegeneration. This gives rise to a “multi-hit” hypothesis whereby two or more factors, for example the accumulation of misfolded protein and glial cell response, are required to trigger neurodegeneration.
Keywords: prion; neurodegeneration; misfolded protein; prion seeds; RT-QuIC